Legal Basis for the Idea of Establishing Specialized Court for Medical Profession - Darto Supadmo; Handoyo Prasetyo (Riviera Publishing, 2024)
This research discusses which laws and regulations can be used as a legal basis for the establishment of Special Medical Courts in Indonesia. The aim of this research is to find out which laws and regulations can be used as a legal basis for the establishment of Special Medical Courts in Indonesia. The method in this research is normative legal research using normative case studies in the form of legal behavior products, for example reviewing laws. The research results obtained are that the laws and regulations that can be used as a legal basis for the establishment of a Special Medical Court in Indonesia are (1) Pancasila and the 1945 Constitution as a philosophical basis, and (2) Article 28D, Article 28 H (paragraph) 1 Constitution of 1945, Law Number 29 of 2004 concerning Medical Practice, Law no. 48 of 2009 concerning Judicial Power, Law no. 36 of 2009 concerning Health, Law Number 44 of 2009 concerning Hospitals, Law Number 36 of 2014 concerning Health Workers as jurisdiction.